Canna (Canna edulis) Flour's Properties as Indonesian Functional Food to Lower Colorectal Cancer Risk - Jessica Natalie Santoso; Steffany Soegijanto; Angelica Gabriel Eldyjoe; Helena Felicia; Gabriella Jovita Kusuma; Rini Wiranti; Junaida Astina (Universitas Bio Scientia Internasional Indonesia, 2025)
The imbalanced food supply in Indonesia has posed a significant challenge. The utilization of canna (Canna Edulis) starch can act as a potential solution, enabling society to consume a more diverse variety of commodities rather than relying solely on rice. Canna, an underutilized tuber, is rich in resistant starch and bioactive compounds, showing potential in tackling dietary and health issues. Despite its high glycemic index, efforts to modify canna starch into resistant starch aim to enhance its health benefits by improving blood sugar control and gut health. This paper aims to introduce ganyong (Canna edulis) starch as a versatile alternative to rice or wheat for carbohydrates, which also highlights the urgent need to address and prevent the high prevalence of colorectal cancer in society by the role of bioactivity and mechanisms of action of canna starch. The applications of canna starch in the food industry such as ginger bangket biscuits, cendol, and cookies, is discussed to highlight its potential as a substitute for traditional starch sources, along with its sensory attributes. Although limitations are acknowledged, continued research and development in processing techniques are essential to unlock the full potential of canna starch and its application in addressing food security and health challenges.